Antropometry and physical conditions of dominant determination on basketball athlete - Ardhian Tomy Kurniawan; M. Furqon Hidayatullah; Muchsin Doewes (Kazimierz Wielki University, 2019)
The purpose of this study was to determine anthropometry and dominant physical conditions to determine the achievement of 12-16 year old basketball athletes. This study used a population of basketball players aged 12-16 years in basketball clubs in Solo Raya, which numbered 60 players. The sampling technique in this study used a purposive sampling technique. The technique of collecting data uses tests and measurements. Factor analysis in this study was carried out using the SPSS version 20.0 program with KMO and Bartlett's Test. The results showed that after analyzed using confirmatory factor analysis with KMO and Bartlett's Test, the dominant anthropometric factors had an effect on basketball games, namely arm range, height, length of leg, leg length, foot length, weight, and width of the foot. While the dominant physical condition factors influence basketball games, namely arm power, leg power, speed and agility. There are two factors in physical conditions which are included in the category of weak or less dominant after the athlete 12-16 years are flexibility in the box, and hand eye coordination.